1999
DOI: 10.1002/(sici)1099-1166(199909)14:9<739::aid-gps998>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of depression among Saudi elderly

Abstract: Objectives To assess the prevalence of depression and associated factors in elderly people in Saudi Arabia. Method A cross‐sectional national survey of the elderly population of Saudi Arabia was conducted between January 1994 and December 1995. A stratified two‐stage sampling technique was used to select the study subjects. In the first stage, a random sample of primary health care centres (PHCs) was selected in each of the five administrative regions of the country. The family health records (FHR) of each sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
83
4
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(115 citation statements)
references
References 26 publications
17
83
4
11
Order By: Relevance
“…Depression correlated with poor education, unemployment (p ¼ 0.001), divorced old age and female sex. 20 These findings are similar to ours, especially if one factors in the study by Al-Shammari and Al-Subaie 20 which reported that perception of poor health and dependence on others for daily activities were associated with more depressive symptoms (p ¼ 0.001). These factors apply to our chronic dialysis patients who have many comorbid conditions and are often dependent on others.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Depression correlated with poor education, unemployment (p ¼ 0.001), divorced old age and female sex. 20 These findings are similar to ours, especially if one factors in the study by Al-Shammari and Al-Subaie 20 which reported that perception of poor health and dependence on others for daily activities were associated with more depressive symptoms (p ¼ 0.001). These factors apply to our chronic dialysis patients who have many comorbid conditions and are often dependent on others.…”
Section: Discussionsupporting
confidence: 88%
“…Nevertheless, a cross-sectional survey carried out in a large number of primary healthcare patients in Saudi Arabia using GDS scale 20 showed that this tool is appropriate in that population with depressive symptoms seen in 39% of the subjects studied of whom 8.4% were in the severe depressive symptoms score group. Depression correlated with poor education, unemployment (p ¼ 0.001), divorced old age and female sex.…”
Section: Discussionmentioning
confidence: 99%
“…Current available data covers only depression among older adults in the KSA, which ranges from 18% 48 to 39% 49 . The low number of geriatric patients utilizing mental health care services may be attributable to their preference for general practitioners or other non-psychiatric doctors for their multiple and unexplained physical complaints 13,50 ; in addition, many developing countries have observed a lack of specialized mental health services for older people 51 .…”
Section: Discussionmentioning
confidence: 99%
“…34 En términos de la concordancia del punto de corte seleccionado con los criterios de referencia (ICD-10 y DSM-IV), los coeficientes kappa estimados muestran que dicha concordancia no se debió al azar, 35 mientras que para la consistencia interna del CESD-7, el valor estimado del alfa de Cronbach fue también aceptable. 36 Con respecto a la prevalencia estimada de SDCS con este punto de corte (41%), diversos estudios, utilizando instrumentos breves de tamizaje similares, han encontrado prevalencias comparables a las que se reporta en este estudio, [37][38][39][40][41][42][43][44] aunque el rango reportado es más amplio, entre 19 y 66%. Estos datos sugieren que la prevalencia reportada en este estudio sigue una tendencia común dentro de la población de adultos mayores.…”
Section: Conclusionesunclassified